Effect of planting distance on yield cassava foliage it's replacement to brewer's grain as protein supplement on growth of yellow cattle fed basal diet of cassava pulp-urea and rice-straw : - Keopaseuth, Toum (Can Tho University, 2017)
Contents: Paper 1: Effect of planting distance on foliage yeild of cassava (Manihot Esculenta Crantz). Paper 2Cassava (Manihot Esculenta Crantz) foliage replacing brewer's grains as protein supplement for Yellow cattle fed a basal diet of cassava pulp-urea and rice straw